Cinacalcet use in paediatric dialysis: a position statement from the European Society for Paediatric Nephrology and the Chronic Kidney Disease-Mineral and Bone Disorders Working Group of the ERA-EDTA - Bacchetta, Justine; Schmitt, Claus P.; Ariceta, Gema; Bakkaloglu, Sevcan A.; Groothoff, Jaap; Wan, Mandy; Vervloet, Marc; Shroff, Rukshana; Haffner, Dieter (Nephrology, dialysis, transplantation, 2019)
Secondary hyperparathyroidism (SHPT) is an important complication of advanced chronic kidney disease (CKD) in children, which is often difficult to treat with conventional therapy. The calcimimetic cinacalcet is an allosteric modulator of the calcium-sensing receptor. It has proven to be effective and safe in adults to suppress parathyroid hormone (PTH), but data on its use in children are limited. To date, studies in children only consist of two randomized controlled trials, nine uncontrolled interventional or observational studies, and case reports that report the efficacy of cinacalcet as a PTH-lowering compound. In 2017, the European Medical Agency approved the use of cinacalcet for the treatment of SHPT in children on dialysis in whom SHPT is not adequately controlled with standard therapy. Since evidence-based guidelines are so far lacking, we present a position statement on the use of cinacalcet in paediatric dialysis patients based on the available evidence and opinion of experts from the European Society for Paediatric Nephrology, Chronic Kidney Disease-Mineral and Bone Disorder and Dialysis Working Groups, and the ERA-EDTA. Given the limited available evidence the strength of these statements are weak to moderate, and must be carefully considered by the treating physician and adapted to individual patient needs as appropriate. Audit and research recommendations to study key outcome measures in paediatric dialysis patients receiving cinacalcet are suggested.
Gesehen am 29.10.2020